Sortie : le magazine qui sort de l'ordinaire. (Montréal : Les productions C.C., 1985)
Fonds Suzan Daniel (FSD)
Periodiciteit : 10x/jaar
Redactie : 3961 rue Saint-Denis, Montréal, QC H2W 2M4
Frans
Periodiek